Competition exercises and its impact on the development of speed endurance and dribbling that ends with accurate scoring and some offensive skills for young players in handball - Naktal Muzahem Khaleel; Wissam Mahdi Saleh; Songol Bilal Murad (Zien Journals, 2022)
Identifying competition exercises and its impact on developing speed endurance and dribbling that ends with accurate scoring for young handball players. Identifying competition exercises and its impact on developing some offensive skills for young handball players
Keywords: competitive; endurance; handball; offensive skills